The impact of Thyroid function on individuals reduced physical strength and obesity in Baghdad: تأثير وظيفة الغدة الدرقية على الأفراد الذين يعانون من انخفاض القوة البدنية والسمنة (Samarra Journal of Pure and Applied Science, 2026)
This study was conducted in Baghdad, Iraq, over a period of time extending from the 1 / November/ 2024 to 25 /February /2025 among individuals within the community in Baghdad, Iraq. This study takes Ninety blood sample were collected and divided into three groups (30 sample from the control group, 30 sample from the skinny group and 30 sample from the obesity group) from the community with attached personal information. All laboratory tests were analyzed in the laboratories of the College of Medical Technology/ Al-Farahidi University/Baghdad. The thyroid hormone analyses were performed using Fine-care technique. The results appear a significant increase in BMI (P > 0.05) and Thyroid-stimulating hormone (P > 0.05), while there were no significant differences with triiodothyronine (T3) hormone (P0.05) and TSH hormone (P>0.05), while age hasn't statistically significant with T3 hormone (P